Moving Margins: Writing in Relation as Liberatory Practice - Saba Hamzah; Kolar Aparna (Social Inclusion)
This article is a practice of writing in relation. We consciously keep the conversational format to be close to our practice as educators, migrant‐artists, and scholars. We weave our personal journeys as political and urgent for epistemic justice on questions of social inclusion of (forced) migrants. We do so to question the dominant forms of inclusion practiced in institutions that our bodies have navigated and continue to do so. Our intention is to open rather than fix our approach of relational biographical writing to bring attention to some hidden forms of daily violence and paradoxes challenging the path of emancipatory practice within spaces claiming social inclusion of migrants/refugees. We reflect on why we write and why we came to academia, inviting the reader to journey with us in what we experience as moving margins.